Mixotrophic Growth Under Micro-Oxic Conditions in the Purple Sulfur Bacterium “Thiodictyon syntrophicum” - Luedin, Samuel M.; Storelli, Nicola; Danza, Francesco; Roman, Samuele; Wittwer, Matthias; Pothier, Joël F.; Tonolla, Mauro (Frontiers in Microbiology, 2019)
The microbial ecosystem of the meromictic Lake Cadagno (Ticino, Swiss Alps) has been studied intensively in order to understand structure and functioning of the anoxygenic phototrophic sulfur bacteria community living in the chemocline. It has been found that the purple sulfur bacterium “Thiodictyon syntrophicum” strain Cad16T, belonging to the Chromatiaceae, fixes around 26% of all bulk inorganic carbon in the chemocline, both during day and night. With this study, we elucidated for the first time the mode of carbon fixation of str. Cad16T under micro-oxic conditions with a combination of long-term monitoring of key physicochemical parameters with CTD, 14C-incorporation experiments and quantitative proteomics using in-situ dialysis bag incubations of str. Cad16Tpure cultures. Regular vertical CTD profiling during the study period in summer 2017 revealed that the chemocline sank from 12 to 14 m which was accompanied by a bloom of cyanobacteria and the subsequent oxygenation of the deeper water column. Sampling was performed both day and night. CO2 assimilation rates were higher during the light period, both in the chemocline population and in the incubated cultures. The relative change in the proteome between the two conditions (663 quantified proteins) comprised only 1% of all CDS encoded in str. Cad16T. Oxidative respiration pathways were upregulated at light, whereas stress-related mechanisms prevailed during the night. These results indicate that low light availability and the co-occurring oxygenation of the chemocline induced mixotrophic growth in str. Cad16T. Our study thereby helps to further understand the consequences micro-oxic conditions for phototrophic sulfur oxidizing bacteria. The complete proteome data have been deposited to the ProteomeXchange database with identifier PXD010641.